2017
DOI: 10.1007/s00382-017-3810-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arctic geoengineering on precipitation in the tropical monsoon regions

Abstract: due to Arctic geoengineering, but there is still a residual precipitation increase (up to 7%) in most monsoon regions associated with the residual CO 2 induced warming in the tropics. The ITCZ shift due to our Global geoengineering simulation, where aerosols (20 Mt) are prescribed uniformly around the globe, is much smaller and the precipitation changes in most monsoon regions are within ±2% as the residual CO 2 -induced warming in the tropics is also much less than in Arctic and Polar geoengineering. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 65 publications
5
66
0
Order By: Relevance
“…The mass of aerosol was chosen based on Nalam et al (2017), where they prescribed 20 Tg of background sulfate aerosols in five layers centered at 37 hPa to offset the global mean surface temperature change caused by a doubling of CO 2 . In CAM4, the sulfate aerosols are log-normally distributed with fixed size distributions (Neale et al, 2010). For our stratospheric aerosol experiments, we use volcanic aerosols which have an effective mean radius of 0.426 µm and a geometric standard deviation of 1.25.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass of aerosol was chosen based on Nalam et al (2017), where they prescribed 20 Tg of background sulfate aerosols in five layers centered at 37 hPa to offset the global mean surface temperature change caused by a doubling of CO 2 . In CAM4, the sulfate aerosols are log-normally distributed with fixed size distributions (Neale et al, 2010). For our stratospheric aerosol experiments, we use volcanic aerosols which have an effective mean radius of 0.426 µm and a geometric standard deviation of 1.25.…”
Section: Experimental Designmentioning
confidence: 99%
“…For our stratospheric aerosol experiments, we use volcanic aerosols which have an effective mean radius of 0.426 µm and a geometric standard deviation of 1.25. The mass of the aerosols consists of 75 % H 2 SO 4 and 25 % H 2 O (Neale et al, 2010). The zonal variations as well as interannual variations (for this study) in mixing ratio of the volcanic aerosols are omitted (Ammann et al, 2003;Neale et al, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
“…It is defined as the median latitude of zonal mean area-weighted precipitation between 20°S and 20°N. In order to identify small shifts in the ITCZ position, we interpolate the ∼2°latitude grid in to a 0.01°grid (Donohoe et al 2013, Devaraju et al 2015, Nalam et al 2018.…”
Section: How Much Does the Itcz Shifts?mentioning
confidence: 99%
“…We also estimate the corresponding annual mean northward heat transport (Donohoe et al 2013, Nalam et al 2018 in the 60×BC case (figure S14). We find that for a ∼7°shift in the ITCZ position, the magnitude of annual mean cross-equatorial atmospheric northward heat transport (AHTeq) to the SH from the NH is ∼−1.2 PW.…”
Section: How Much Does the Itcz Shifts?mentioning
confidence: 99%
“…Studies have shown that the addition of sulfate aerosols into the stratosphere could offset the CO 2 -induced global mean warming but usually at the cost of a reduced intensity of global hydrological cycle mainly associated with the fast climate adjustments (e.g., Duan et al, 2018;Ferraro & Griffiths, 2016;Kalidindi et al, 2015;Myhre et al, 2018). Also, stratospheric aerosol geoengineering can induce changes in stratospheric ozone concentration and large-scale stratospheric circulation due to the change in stratospheric temperature, water vapor content, and heating rate (Ferraro et al, 2015;Kalidindi et al, 2015;Krishna-Pillai Sukumara-Pillai et al, 2019;Madronich et al, 2018;Nalam et al, 2017;Pitari et al, 2014;Richter et al, 2017;Simone Tilmes et al, 2009). A number of recent studies have shown that multiple temperature goals could be achieved by interactively adjusting the location and rate of sulfate aerosol injections, indicating the possibility to achieve multiple regional climate mitigation goals (e.g., Kravitz the climate response, SAI geoengineering has been simulated with multiple climate models using the same experimental protocol under the framework of the Geoengineering Model Intercomparison Project (e.g., Kravitz et al, 2011Kravitz et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%